7D.07: RETINAL ARTERIOLAR STRUCTURE IN PATIENTS WITH PHEOCHROMOCYTOMA. (June 2015) - Prejbisz, A.; Harazny, J.; Szymanek, K.; Binczyk, E.; Gosk-Przybylek, M.; Szaflik, J.; Kasperlik-Zaluska, A.; Peczkowska, M.; Otto, M.; Kabat, M.; Warchol-Celinska, E.; Eisenhofer, G.; et al.
Abstract : Objective: The aim of the ongoing study is to analyze retinal arteriolar structure in patients with pheochromocytoma (Pheo), a form of secondary hypertension characterized by excessive catecholamine secretion as compared with well-matched patients with essential hypertension (EHT). Figure. No caption available. Design and method: We examined 24 (15f/9m) patients with Pheo (mean age 46.3 ± 11.8 years) and 24 (15f/9m) age, gender, body mass index, glycemic status and blood pressure levels matched patients (46.7 ± 12.0 years) with (EHT). In all patients evaluation of plasma free normetanephrine (NMN) and metanephrine (MN) concentrations by liquid chromatography with tandem mass spectrometry was performed. Diagnosis of pheochromocytoma was made based on increased free NMN and/or MN concentration and confirmed on pathological examination. Retinal arterioles morphology were assessed by Heidelberg Retina Flowmetry using scanning laser Doppler flowmetry (SLDF). Outer diameter (AD) and lumen diameter (LD) were measured with automatic full-field perfusion imaging analysis (AFFPIA). Wall-to-lumen ratio (WLR), wall thickness (WT) and wall cross-sectional area (WCSA) of retinal arterioles were calculated. Retinal capillary blood flow (RCF) was also assessed by SLDF. Results: Pheo and EHT groups were well matched for age, gender, BMI, office and ambulatory blood pressure levels as well as for glycemic status and number of hypertensive medication (p > 0.05 for all comparisons). Patients with pheochromocytoma were characterized by higher AD, LD, WT and WCSA as compared with EHT (Table). A tendency towards higher WLR in patients with pheochromocytoma as compared to EHT was also noted (Table). There was no difference in RCF between patients with pheochromocytoma and EHT. Conclusions: Patients with pheochromocytoma as compared with matched patients with essential hypertension are characterized by higher outer wall diameter, lumen diameter, higher wall thickness and higher wall cross-sectional area of retinal arterioles. This may indicate potential deleterious effect of high catecholamine levels on small caliber arterioles evaluated non-invasively by SLDF.